Gender-typical olfactory regulation of sexual behavior in goldfish - Kawaguchi, Yutaro; Nagaoka, Akira; Kitami, Asana; Mitsuhashi, Tomomi; Hayakawa, Youichi; Kobayashi, Makito (Frontiers in Neuroscience, 2014)
It is known that olfaction is essential for the occurrence of sexual behavior in male goldfish. Sex pheromones from ovulatory females elicit male sexual behavior, chasing and sperm releasing act. In female goldfish, ovarian prostaglandin F2α (PGF) elicits female sexual behavior, egg releasing act. It has been considered that olfaction does not affect sexual behavior in female goldfish. In the present study, we reexamined the involvement of olfaction in sexual behavior of female goldfish. Olfaction was blocked in male and female goldfish by two methods: nasal occlusion (NO) which blocks the reception of olfactants, and olfactory tract section (OTX) which blocks transmission of olfactory information from the olfactory bulb to the telencephalon. Sexual behavior of goldfish was induced by administration of PGF to females, an established method for inducing goldfish sexual behavior in both sexes. Sexual behavior in males was suppressed by NO and OTX as previously reported because of lack of pheromone stimulation. In females, NO suppressed sexual behavior but OTX did not affect the occurrence of sexual behavior. Females treated with both NO and OTX performed sexual behavior normally. These results indicate that olfaction is essential in female goldfish to perform sexual behavior as in males but in a different manner. The lack of olfaction in males causes lack of pheromonal stimulation, resulting in no behavior elicited. Whereas the results of female experiments suggest that lack of olfaction in females causes strong inhibition of sexual behavior mediated by the olfactory pathway. Olfactory tract section is considered to block the pathway and remove this inhibition, resulting in the resumption of the behavior. By subtract sectioning of the olfactory tract, it was found that this inhibition was mediated by the medial olfactory tracts, not the lateral olfactory tracts. Thus, it is concluded that goldfish has gender-typical olfactory regulation for sexual behavior.